Analisis Klausa Verbal dalam Teks Deskripsi pada Buku Pendidikan Pancasila dan Kewarganegaraan Kelas X SMA/SMK Kurikulum Merdeka - Lalitta Octavia; Vianni Nifattien Vrisna Putri; Novana Ika Puspita; Elvina Amanda Cahya Dewi; Asep Purwo Yudi Utomo; Didi Pramono (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research is an activity to examine descriptive texts that focus on the area of syntax, which is called verbal clauses. The texts analyzed are descriptive texts about the concept, its importance, and examples of mutual cooperation practices. This research is motivated by the diversity of the use of verbal clauses in descriptive texts. The purpose of this study is to provide insight into the classification of verbal clauses and provide examples of their classification in the descriptive text in the "Class X Citizenship Education of SMA/SMK Merdeka Curriculum Book." The method used in this study is a combination of two approaches: methodological, descriptive, and qualitative, as well as a theoretical approach with a syntactic approach. The data used is in the form of sentences from descriptive texts in the Citizenship Education Class X SMA/SMK Merdeka Curriculum Book and analyzed according to the verbal clause classification. The data source comes from the descriptive text in the book. Techniques using note-taking and listening or reading Techniques Data analysis techniques include data reduction, analysis, interpretation, and triangulation, which are then used to draw a conclusion. The presentation technique is the informal presentation of data. From the results of the data analysis, it can be concluded that there are several forms of verbal clauses in the description text, namely: transitive verbal clauses, intransitive verbal clauses, passive verbal clauses, and reciprocal verbal clauses contained in the description text in the Pancasila and Citizenship Education book for class X of the SMA/SMK Merdeka Curriculum Book. This article can be advantageous for students, especially college students, because it provides insight into the classification of verbal clauses and the use of verbal clauses in the book.